Sarna, Holokaust i nostalgia inteligenta. Wokół Sarniej pułapki Artura Daniela Liskowackiego. Esej zoo(tanato)graficzny (Heteroglossia – studia kulturoznawczo-filologiczne, 2024)
The aim of this article is the micrological reading of Artur Daniel Liskowacki’s essay entitled Sarnia pułapka [Deer Trap] (from the volume Kronika powrotu [Chronicle of Return], 2012). The text under analysis is treated as an example of zoo(thanato)graphy (a term related to Derrida’s and Ubertowska’s formulas), the narration that could be described as the animal posthumous biography. In Deer Trap, Liskowacki makes an attempt to reconstruct the animal perspective, constitute the animal subject, and reflects on the reactions of animals and humans in border situations related to a deadly threat. The element which reconnects the interspecies community is, according to the writer, the physiology of fear. This motif of his considerations leads the author to the studies of war and Holocaust.